Four Jews on Parnassus : a conversation : Benjamin, Adorno, Scholem, Schönberg - Djerassi, Carl (Columbia University Press, 2008)
Theodor W. Adorno was the prototypical German Jewish non-Jew, Walter Benjamin vacillated between German Jew and Jewish German, Gershom Scholem was a committed Zionist, and Arnold Schönberg converted to Protestantism for professional reasons but later returned to Judaism. Carl Djerassi, himself a refugee from Hitler's Austria, dramatizes a dialogue between these four men in which they discuss fraternity, religious identity, and legacy as well as reveal aspects of their lives-notably their relations with their wives-that many have ignored, underemphasized, or misrepresented. The desi.